Temporal Patterns in Blood Pressure Management Before and After Recent Clinical Trials and Guideline Recommendations - Eric J. Brandt; Craig J. Beavers; Zhuxuan Fu; Erica S. Spatz; Philip G. Jones; Suzanne V. Arnold; Nihar R. Desai (The Journal of Clinical Hypertension)
ABSTRACT We aimed to study trends in achieving blood pressure (BP) goals, antihypertensive prescribing, and whether clinician behavior changed in temporal relationship to the JNC‐8 (October 1, 2014), SPRINT results (November 9, 2015), and the 2017 hypertension guideline (November 13, 2017). We used the National Cardiovascular Data Registry (NCDR) Practice INNovation and CLinical Excellence (PINNACLE) registry and studied patients with hypertension aged >65 years (n = 3 678 774). We found a statistically significant, albeit small and minimally relevant, increase from 2013 to 2018 in achieving office‐based SBP.